2017
DOI: 10.1002/ange.201705412
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Nucleophilic Additions of Highly Polar Organometallic Compounds to Imines and Nitriles Using Water as a Non‐Innocent Reaction Medium

Abstract: In contrast to classic methods carried out under inert atmospheres with dry volatile organic solvents and often low temperatures, the addition of highly polar organometallic compounds to non‐activated imines and nitriles proceeds quickly, efficiently, and chemoselectively with a broad range of substrates at room temperature and under air with water as the only reaction medium. Secondary amines and tertiary carbinamines are furnished in yields of up to and over 99 %. The significant solvent D/H isotope effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 36 publications
0
5
0
2
Order By: Relevance
“…Im Gegensatz dazu führten Versuche ohne Wasser zur signifikanten Verringerung beider Werte. [22] Aufd er Basis des sterisch anspruchsvollen C-H-aziden Ligandensystems Bis(4,6-tBu-benzoxazol-2-yl)methanid (1) präsentieren wir hier die erstmalige Synthese einer Organokaliumverbindung in der Gegenwart von Wasser, deren strukturelle Charakterisierung im Folgenden detailliert diskutiert wird. In der Gegenwart von 1.5 ¾quivalenten Wasser konnte selbst bei À70 8 8Cb ereits nach wenigen Minuten eine vollständige Umsetzung in der Methylaluminierung von 1-Hexin beobachtet werden.…”
unclassified
See 1 more Smart Citation
“…Im Gegensatz dazu führten Versuche ohne Wasser zur signifikanten Verringerung beider Werte. [22] Aufd er Basis des sterisch anspruchsvollen C-H-aziden Ligandensystems Bis(4,6-tBu-benzoxazol-2-yl)methanid (1) präsentieren wir hier die erstmalige Synthese einer Organokaliumverbindung in der Gegenwart von Wasser, deren strukturelle Charakterisierung im Folgenden detailliert diskutiert wird. In der Gegenwart von 1.5 ¾quivalenten Wasser konnte selbst bei À70 8 8Cb ereits nach wenigen Minuten eine vollständige Umsetzung in der Methylaluminierung von 1-Hexin beobachtet werden.…”
unclassified
“…[19][20][21] Erst kürzlich konnte sogar über die bis dato präzedenzlose Verwendung puren Wassers als einziges Reaktionsmedium in nucleophilen Additionsreaktionen von Grignard-und Organolithiumreagenzien an Imine,N itrile und Carbonylverbindungenb erichtet werden. [22] Aufd er Basis des sterisch anspruchsvollen C-H-aziden Ligandensystems Bis(4,6-tBu-benzoxazol-2-yl)methanid (1) präsentieren wir hier die erstmalige Synthese einer Organokaliumverbindung in der Gegenwart von Wasser, deren strukturelle Charakterisierung im Folgenden detailliert diskutiert wird.…”
unclassified
“…To gain additional insight into the generality of the ligand effect, we examined the cross‐coupling of 1‐chlorobenzonitrile ( 28 ) at low catalyst loading (Table ). This substrate is sensitive to Grignard nucleophilic addition to the cyano group and the most difficult in the cross‐coupling at low catalyst loading. Pleasingly, we found that TMU ( 1 ) served as a much superior ligand to other ligands, including NMP ( 22 , 33 % yield) and DMI ( 24 , 72 % yield) (not shown) under these conditions.…”
Section: Figurementioning
confidence: 99%
“…A notable exception is represented by the employment of γ-valerolactone as an alternative, non-toxic biomass-derived medium solvent for synthesizing acetylene-containing systems starting from (hetero)aryl iodides. [46] Based on our ongoing interest in using water and DESs to explore novel paradigms in metal-mediated and metalcatalyzed organic transformations, [47][48][49][50][51][52][53][54][55][56][57] herein we report the results of a study demonstrating the usefulness of a recycling biocompatible DES such as ChCl/Gly as an environmentally responsible reaction medium for carrying out ligand-free SH couplings between (hetero)aryl iodides and terminal aryl-or alkyl-substituted alkynes with a broad substrate scope, and working under heterogeneous conditions by using a cheap and recyclable catalyst such as Pd/C (Scheme 1d).…”
mentioning
confidence: 99%